PELATIHAN BUDIDAYA SAYURAN METODE BUDIKDAMBER SKALA RUMAH TANGGA SEBAGAI USAHATANI DAN KONTRIBUSINYATERHADAP PENGELUARAN KONSUMSI RUMAH TANGGA MASYARAKAT DESA PANDAN SARI KECAMATAN SEGAH - Galingging, Herwan; Haq, Arsyadani Sabilal; Hakim, Lukmanul (JURNAL ABDIMAS UNTAG SAMARINDA, 2025)
This community service activity aims to; 1). Providing science material and mastery of Budikdamber aquaponic technology for PKK women in Panda Sari Village, Segah District. 2). Increasing the knowledge and awareness of housewives or PKK mothers that the adequacy of family nutrition can be obtained through the use of narrow yard land. 3). Providing an understanding that Budikdamber method vegetable farming can be a source of income to meet household consumption expenses. 4). Budikdamber method vegetable farming can be a source of income contributing to household consumption expenditure of household consumption every month by 39.95%.